A meta-analysis of the secondary fractures for osteoporotic vertebral compression fractures after percutaneous vertebroplasty. Issue 16 (23rd April 2021) - Zhai, Gongwei; Li, Ang; Liu, Binfeng; Lv, Dongbo; Zhang, Jingyi; Sheng, Weichao; Yang, Guang; Gao, YanZheng
Abstract : Abstract: To identify the risk factors of the secondary fractures for osteoporotic vertebral compression fractures (OVCFs) after percutaneous vertebroplasty (PVP). We conducted a search of relevant articles using Cochrane Library, PubMed, Medline, Science Direct, Embase, the Web of Science and other databases. The time range we retrieved from establishment of the electronic database to November 2017. Gray studies were found in the references of included literature reports. STATA version 11.0 (Stata Corporation, College Station, Texas) was used to analyze the pooled data. Fourteen studies involving 1910 patients, 395 of whom had fracture secondary to the surgery were included in this meta-analysis. The result of meta-analyses showed the risk factors of the secondary fractures for OVCFs after PVP was related to bone mineral density (BMD) [95%CI (−0.650, −0.164), SMD=−0.407, P =.001], cement leakage ((RR=0.596, 95%CI (0.444, 0.798), P = .001)), and kyphosis after primary operation ((SMD=0.741, 95%CI (0.449, 1.032), P = .000)), but not to gender, age, body mass index, cement volume, thoracolumbar spine, and cement injection approaches. Bone mineral density, cement leakage, and kyphosis after primary operation are the risk factors closely correlative to the secondary fracture after PVP. There have not been enough evidences to support the association between the secondary fracture and gender, age, body mass index, cement volume, thoracolumbar spine, and cement injection approaches.